Borderless Bazaars and Regional Integration in Central Asia : Emerging Patterns of Trade and Cross-Border Cooperation - Kaminski, Bartlomiej (Washington, DC: World Bank, 2013)
Local populations' economic opportunities can be enhanced through special arrangements governing movement of people and goods in neighboring areas. For instance, in the Tajikistan-Uzbekistan border-crossing points (BCPs), preferential treatment accorded to residents in contiguous regions varies from one BCP to another, even within one borderline, restricting the distance allowed for travel into the territory of another country to the closest large city or marketplace. When governments impose restrictions on the movements of individuals, vehicles, or goods or close BCPs or bazaars, they may do so on public policy grounds. Security is often cited as a factor for imposing controls, as is prevention of contraband trade. Such government imposed obstacles are a blunt and expensive instrument to attain such public policy aims. The income and welfare costs levied on poor communities of such public policies may be disproportionate to achieve stated public policy goals. Instead, BCPs and bazaars could be opened but made subject to strict and effective policing, ideally using risk-based criteria; similarly, risk-based surveillance or vehicle searches could take the place of an outright ban. Moreover, a government may find that the security benefits of stronger community ties across borders may be considerable; after all, in conditions of growing trade that obviously contributes to the prosperity of a border community, all parties have a stake in suppressing criminal behavior and public disorder and in promoting orderly conditions that minimize the likelihood of the need for security services to intervene. In summary, support for border trade is a win-win strategy for any pair of countries. Government-imposed restrictions may constrict trade and raise its cost, but they do not necessarily eliminate local trade, especially among countries with established cultural, ethnic, and economic ties, which is the case of the former Soviet republics in Central Asia. Such restrictions raise transaction costs and incentivize smuggling. They greatly reduce the beneficial impact on income and employment that can arise from border trade, leading to large welfare losses for communities. The most significant effect of growth in border trade is likely to be poverty reduction in communities in contiguous regions.